Ex-voto d'Italia Strategie di comportamento sociale, per grazia ricevuta - Grimaldi, Renato (Percorsi di ricerca, 2020)
The volume tells us about the close relationship between heaven and earth, between the extraordinary and the everyday, between faith and science, highlighted by the countless episodes of piety that allow us to retrace history and grasp its transformations, starting from the lived life of thousands of protagonists. In fact, the painted votive tablets prove to be an exceptional vector for reproducing and transmitting the values of the community: family, homeland, work, care for animals and the territory, use of means of transport and old and new technologies. In the ex-voto the cycles of life and seasons unfold and the impact on them of small and large natural or social disasters that recur over time with impressive regularity, unfortunately we find ourselves unprepared each time. In dealing with risks and calamities of all kinds, ex-votos women and men look upwards - with great dignity - asking them to survive, persist and replicate themselves as biological entities and cultural entities. The long sequence of events narrated in the ex-votos constitutes a sort of DNA of our nation, indispensable for shaping the country's future. Also for this reason, painted ex-votos must be detected, filed, preserved, protected, valued, studied and brought to the attention of the general public, as this volume proposes.